GAMBARAN KELELAHAN DAN KELUHAN MUSKULOSKELETAL PADA PENGEMUDI BUS MALAM JARAK JAUH PO. RESTU MULYA - Rahmadi Fahmi (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTLong trip night bus drivers is a very highly risk of fatigue and musculoskeletal disorder. The aim of this research was to learn and acknowledging the level of fatigue and musculoskeletal disorder in PO. (Perusahaan Otobus) Restu Mulya long trip night bus drivers. This is an observational descriptive research with cross sectional study design. The research’s variable is the level of fatigue and musculoskeletal disorder that obtained from primary data using SSRT (Subjective Self Rating Test) questionnaire and NBM (Nordic Body Map) questionnaire. The result shows that 58.33% long trip night bus drivers was felt a moderate level of fatigue and 41.67% long trip night bus drivers felt a severe level of  fatigue. Most of long trip night bus drivers which number 75% drivers felt almost-sick of musculoskeletal disorder with the buttock, back, neck, and leg symptom point. The fatigue in PO. Restu Mulya long trip night bus drivers was a moderate and severe level with a lower activity and physicly fatigue symptom. The fatigue can be possibly caused by high physical work burden and psycologycal work burden which is a big responsibilities for the passengers safety. Then a low level of musculoskeletal disorders with the buttock, back, neck, and leg symptom point that possibly caused by monotony sit work posture on a very long time.Keywords: long trip night bus drivers, fatigue, musculoskeletal disorder